Obesity indices as predictors of pattern of self-reported arthritis among elderly women in Southwestern Nigeria - Adebimpe, Wasiu O (SAGE Open Med, 2015)
OBJECTIVES: This study assessed obesity indices and pattern of arthritis among elderly women in Osun State, Southwestern Nigeria. METHODS: The cross-sectional descriptive study was carried out among 350 elderly women selected by multistage sampling technique. Research instruments used in data collection were semi-structured, interviewer-administered pre-tested questionnaires that were analyzed using the Statistical Package for Social Sciences software version 17.0. RESULTS: The mean age of the participants was 69.1 (±1.4) years. A total of 232 (66.3%) of them had complaints of joint pains (Awoka as expressed in the local language). Pattern of arthritis showed that 172 (74.0%) had recurrent joint pains, while 35 (15.1%) had joint swelling; the knee joint was mostly affected. A total of 97 (28.0%) were overweight while 84 (24.0%) were obese. Obese women were twice more likely to have arthritis when compared to the nonobese (odds ratio: 2.4, 95% confidence interval: 1.8–9.4, p = 0.001). CONCLUSION: There is a need to give high priority to weight reduction strategies targeted at the elderly and the entire population.